0607 Clinical Phenotypes of OSA in Diverse Hispanics/Latinos: Results from the Hispanic Community Health Study/Study of Latinos. (27th May 2020) - Gonzalez, K T; Tarraf, W; Wallace, D M; Stickel, A; Schneiderman, N; Redline, S; Patel, S R; Gallo, L C; Mossavar-Rahmani, Y; Daviglus, M; Zee, P C; Talavera, G A; et al.
Abstract: Introduction: Recent work on US non-Latino Whites and Europeans from clinical samples used obstructive sleep apnea (OSA) symptoms to generate OSA phenotypes for individuals with moderate-severe OSA and proposed between 3-5 clusters. Validating these clusters in a diverse Hispanic/Latino community-based population with different biopsychosocial characteristics is crucial for early OSA identification and more personalized treatment. Methods: This work is based on baseline data from The Hispanic Community Health Study/Study of Latinos (HCHS/SOL). HCHS/SOL is a prospective cohort study designed using a multisite (Bronx, NY, Chicago, IL, Miami, FL, San Diego, CA) multistage probability sample. The subpopulation of interest included adults 18-74 years (unweighted n=1, 623) meeting criteria for moderate-severe OSA symptoms (≥15 Apnea-Hypopnea index (AHI) events per hour). We performed latent class analysis (LCA) using 15 common OSA symptoms to identify phenotype clusters. Results: Average age was 52.4 ± 13.9 years and 34.1% were female. Mean AHI was 33.8 ± 22.5 events per hour. Fit statistics and clinical significance suggested that a three-class solution provided best fit to the data. The symptom profiles were consistent with (1) a Minimally Symptomatic group (46.8%), (2) a Disturbed Sleep group (38.1%), and (3) a Daytime Sleepiness group (15.1%). Validation analyses using alternative hierarchical and partitioning algorithms also suggested support for a three-class solution. Conclusion: Sleep apnea phenotypes among diverse Hispanics/Latinos were consistent with recent findings from the Sleep Apnea Global Interdisciplinary Consortium. However, we found notable differences in the prevalence of these clusters relative to Whites. This suggests that other biopsychosocial factors may be contributing to OSA phenotypes among Hispanics/Latinos. Identification of OSA phenotypes in Hispanics/Latinos could inform better sleep interventions and therapeutics and help better align public health resources. Support: 5R01AG048642-05; R21AG056952; R21HL140437.